Scientific basis for use of Pyrus pashia Buch.-Ham. ex D. Don. fruit in gastrointestinal, respiratory and cardiovascular ailments - Janbaz, Khalid Hussain; Ahsan, Muhammad Zaeem; Saqib, Fatima; Imran, Imran; Zia-Ul-Haq, Muhammad; Rashid, Muhammad Abid; Jaafar, Hawa Z. E.; Moga, Marius (Public Library of Science, 2015)
Background Pyrus pashia Buch.-Ham. ex D. Don. has been used conventionally by many communities in the Himalayan region for the management of gastrointestinal, respiratory, and vascular complications. Set against this background, this study was carried out to justify the scientific basis to validate folkloric uses of fruits of Pyrus pashia Buch.-Ham. ex D. Don. (Pp.Cr) in traditional systems of medicine. Methods The crude ethanol extract of fruits of Pyrus pashia Buch.-Ham. ex D. Don. (Pp.Cr) was tested in vitro on isolated rabbit jejunum, tracheal, and aorta preparations. The responses of tissues were recorded using isotonic transducers coupled with a PowerLab data acquisition system. Results The Pp.Cr on application (0.01–5.0 mg/ml) to isolated rabbit jejunum preparation exhibited relaxation through decrease in magnitude and frequency of spontaneous contractions. The Pp.Cr also exerted a relaxant (0.01–5.0 mg/ml) effect on K+(80 mM) induced contractions in isolated rabbit jejunum preparations and caused shifting of the Ca2+ curves (1.0–3.0 mg/ml) toward right in a manner similar to that of verapamil (3μM), possibly suggesting presence of Ca2+ channel blocking activity. Subsequently, Pp.Cr in a concentration-dependent fashion (0.01–10.0 mg/ml) caused relaxation of CCh (1μM) and K+ (80 mM) induced contractions in isolated rabbit tracheal preparations in a manner comparable to that of dicyclomine, suggesting that the observed relaxant effect is likely to be mediated through antimuscarinic and/or Ca2+ channel blocking activities. Moreover, when evaluated against isolated rabbit aortic preparations, the Pp.Cr in concentrations up to 10 mg/ml exhibited a contractile response that was found to be abolished subsequent to pretreatment of isolated tissue preparation with cyproheptadine (1μM), phentolamine (1μM), and losartan (1μM), suggesting that Pp.Cr may have some α-adrenergic, muscarinic, serotonergic, and angiotensin II activities. Conclusions The aqueous ethanolic extract of Pyrus pashia (Pp.Cr) exhibited spasmolytic, bronchodilator, and vaso-constrictive activities possibly through different mechanisms. The spasmolytic and bronchodilator activities are likely to be mediated through blockade of Ca2+ channels, while vasoconstrictive activity may be due to presence of a α-adrenergic, muscarinic, serotonergic, and angiotensin II agonistic component.